Genomic population structure of Helicobacter pylori Shanghai isolates and identification of genomic features uniquely linked with pathogenicity - Feng Yang; Jinghao Zhang; Su Wang; Zhaoyang Sun; Jun Zhou; Feng Li; Yue Liu; Li Ding; Yixin Liu; Wenjing Chi; Tao Liu; Yongqun He; et al. (Taylor & Francis, 2021)
Severe Helicobacter pylori-linked gastric disorders are especially prevalent in the East Asia region. The ability of H. pylori to cause different clinical outcomes is thought to be associated with unique sets of its genetic features. However, only few genetic features have been definitively linked to specific gastrointestinal pathologies. Genome heterogeneity of clinical H. pylori strains from patients with four different gastric disorders was studied to explore the population structure and molecular genomic features and their association with pathogenicity. Population analysis showed that 92.9% of the Shanghai H. pylori isolates were clustered in the East Asia group. Among 2,866 genes detected in all genomes, 1,146 genes formed the core genome, whereas 209 unique genes were detected in individual disease groups. The unique genes of peptic ulcer and gastric cancer groups represented the inorganic ion transport and metabolism function gene clusters. Sixteen virulence genes were detected with statistically different detection rates among the four disease groups. Furthermore, 127 clustered regularly interspaced short palindromic repeats were found with significantly different rates in the four disease groups. A total of 337 putative genomic islands were identified, and three genomic islands were individually found in more than 10% of strains. The genomic islands included several metabolism-associated genes and many genes with unknown function. In total, 88 sequence types were detected among the 112 Shanghai H. pylori isolates. Our study provides an essential milestone in the mapping of specific genomic features and their functions to identify factors needed to induce specific gastric disorders in H. pylori.
Keywords: Space Science; Medicine; Microbiology; Genetics; Chemical Sciences not elsewhere classified; Ecology; Biological Sciences not elsewhere classified; Cancer; Infectious Diseases; Virology